The embattled but empowered community : comparing understandings of spiritual power in Argentine popular and pentecostal cosmologies - Davies, Wilma Wells. (Global Pentecostal and Charismatic Studies, 2010)
The global phenomenon of Pentecostal growth continues to interest scholars, particularly its local manifestations. Although previous explanations may have noted the connections between the cultural substrata and local Pentecostal practices, this book concentrates on seeking out the connections. Using both extensive field research and reflection on Latin American scholarship, the author proposes that a major link exists at the level of worldview assumptions, particularly in understandings of spiritual power. The book concludes with a reflection on the implications a conversion based on the search for spiritual power has for the future of the evangelical church in Latin America.